Analysis of Factors Influencing Stunted Toddlers in the City of Mojokerto - Wardani, Riska Aprilia; Virgia, Vera; Herlina, Herlina (Jurnal MIDPRO, 2022)
Â Overcoming the incidence of stunted children under five is one of the achievement targets in SGDs 2030, namely the social pillar with the achievement target of eliminating hunger and ensuring access for all people, especially the poor and those in vulnerable situations, including babies, to safe, nutritious and sufficient food. throughout the year. One of the indicators for the 2030 SGDs target is the reduced prevalence of stunting among toddlers in Indonesia. Along with this, improving the nutritional status of the community, including reducing the prevalence of stunting under five, is one of the priority national development efforts listed in the main targets of the RJPM. Some of the factors identified as having an effect on the incidence of stunted children are the sex of the toddler, the age of the toddler, family status and family income. The research design used was a retrospective cohort study with a cross sectional approach. The sampling technique used is nonprobability sampling with purposive sampling. The sample in this study were some toddlers at the Balongrawe Posyandu, Kedundung Village, Magersari District, Mojokerto City who met the research criteria as many as 56 respondents. The variables that were studied in this study were the nutritional status of the toddler, the gender of the toddler, the age of the toddler, family status and family income. Test data analysis using binary logistic regression with a significance of Î± (0.05). From the results of the logistic binary regression test, it was found that the dominant factor that influences the incidence of stunted toddlers in toddlers in Mojokerto City is the family status of toddlers with a p value of 0.019 <Î± (0.05) so it can be concluded that family status has a significant partial influence on the incidence stunted toddlers in toddlers in Mojokerto CityÂ Keywords : Family Status, Family Income, Stunted